Attenuation of Acute Lung Inflammation and Injury by Whole Body Cooling in a Rat Heatstroke Model. (17th November 2009) - Yang, Hsi-Hsing; Chang, Ching-Ping; Cheng, Ruei-Tang; Lin, Mao-Tsun
Abstract : Whole body cooling is the current therapy of choice for heatstroke because the therapeutic agents are not available. In this study, we assessed the effects of whole body cooling on several indices of acute lung inflammation and injury which might occur during heatstroke. Anesthetized rats were randomized into the following groups and given (a) no treatment or (b) whole body cooling immediately after onset of heatstroke. As compared with the normothermic controls, the untreated heatstroke rats had higher levels of pleural exudates volume and polymorphonuclear cell numbers, lung myloperoxidase activity and inducible nitric oxide synthase expression, histologic lung injury score, and bronchoalveolar proinflammatory cytokines and glutamate, andPa CO 2 . In contrast, the values of mean arterial pressure, heart rate, PaO 2, pH, and bloodHCO 3 − were all significantly lower during heatstroke. The acute lung inflammation and injury and electrolyte imbalance that occurred during heatstroke were significantly reduced by whole body cooling. In conclusion, we identified heat-induced acute lung inflammation and injury and electrolyte imbalance could be ameliorated by whole body cooling.